Pengaruh Literasi Finansial Terhadap Keberlangsungan Usaha Pada UMKM - Eliza, Mega Sifa; Astuti, Sri; Safitri, Camelia (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
The economy is an important substance for every broad community, where it is implemented in various sectors of life today. MSMEs became pioneers in economic emergencies in the past, until now MSMEs are still able to become the largest contributor to the national economy (GDP) in Indonesia. This is supported by the knowledge, skills, and beliefs of MSME actors regarding their financial literacy.  The purpose of this study was to determine whether there is an effect of financial literacy on business continuity owned by MSMEs Bazar Minggu Ria. This research uses a quantitative approach, the data collection techniques used in this research are library research and field research by distributing questionnaires to samples that have been determined through probability sampling and the analysis used is using descriptive statistics through simple linear regression. The results of this study indicate that t-count> t-table (5.727> 1.66) so that it is concluded that financial literacy has a significant effect on business continuity, where Hα is accepted and H0 is rejected. The financial literacy affects business continuity by 31.6% while the other 68.4% is influenced by other factors not examined in this study.